2015
DOI: 10.1017/s1368980015000361
|View full text |Cite
|
Sign up to set email alerts
|

Trends in socio-economic inequalities in the Scottish diet: 2001–2009

Abstract: 348 g), brown/ wholemeal bread (17 g, 26·5 g), breakfast cereals (16 g, 27 g) and oil-rich (21 g, 40 g) and white fish (77 g, 112 g) were lowest, and that of total bread highest (105 g, 91·5 g) in the most deprived compared with the least deprived households, respectively, for the period [2007][2008][2009]. With regard to nutrients, there was no association between deprivation and the percentage of food energy from total fat and saturated fat; however, non-milk extrinsic sugar intakes (15·5 %, 14·3 %) and ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…Our research confirms previous work that the average UK diet does not meet dietary guidelines [31,53,54]. However, contrary to previous research, it would appear that it is possible to purchase a diet that is healthy and sustainable at a relative low cost.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our research confirms previous work that the average UK diet does not meet dietary guidelines [31,53,54]. However, contrary to previous research, it would appear that it is possible to purchase a diet that is healthy and sustainable at a relative low cost.…”
Section: Discussionsupporting
confidence: 69%
“…The study used purchase data from a large representative sample of the UK population. It has been suggested that purchase data is less subject to bias than individual food diaries [31,49], but as it combines data from purchase diaries within households, it is not possible to see the individual diets of household members or adjust for household composition or ages within the household. In addition, it is not possible to determine how much, if any, food and drink may have been purchased for friends and family outside the household, or whether the purchases were consumed within the 2-week recording period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the relative cost of a high-quality diet increased in the UK (and other high income countries) from the 1990s–2010,[58] although it is unclear if this was matched by increased inequalities in dietary intake. [14, 59] In addition, studies have suggested that there have been increasing cultural expectations from the 1970s onwards for women to be thin,[60] yet for men to be muscular. [61, 62] Since women of higher SEP are likely to have had greater resources to follow these trends, these changes could explain the increasing inequalities observed in the 1970 BCS compared with earlier born cohorts; mean BMI in the most advantaged group remained similar in all three cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In Scotland, CRC risk is associated with increasing deprivation in men (3) , which may be partly attributable to a higher BMI, as well as smoking (4) . A low socio-economic status has also been linked with a reduced consumption of fruit, vegetables, wholemeal bread and fibre and an increased consumption of fat, meat, processed meat and sugar (5)(6)(7)(8)(9)(10)(11)(12) . However, those individuals from more deprived backgrounds may also face a wide range of barriers to a healthy lifestyle, such as food prices (13)(14)(15)(16)(17) , a lack of local facilities (18) , pre-existing health problems (19) , lower education (11) and lower self-efficacy (20,21) .…”
Section: Introductionmentioning
confidence: 99%